6X-5((X+2)-2)=

Simple and best practice solution for 6X-5((X+2)-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6X-5((X+2)-2)= equation:


Simplifying
6X + -5((X + 2) + -2) = 0

Reorder the terms:
6X + -5((2 + X) + -2) = 0

Remove parenthesis around (2 + X)
6X + -5(2 + X + -2) = 0

Reorder the terms:
6X + -5(2 + -2 + X) = 0

Combine like terms: 2 + -2 = 0
6X + -5(0 + X) = 0
6X + -5(X) = 0

Combine like terms: 6X + -5X = 1X
1X = 0

Solving
1X = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Divide each side by '1'.
X = 0

Simplifying
X = 0

See similar equations:

| x^2-5y^2+1=0 | | 0=-1.75d+25 | | -25=-1.75d | | 6X-5(X-2)= | | 93.2x=25x+15 | | 6-8x=117-29x | | 6-8x=177-29x | | 5w^2-20w=0 | | 1500=1.80x+120 | | x*5+20= | | 1110=1.25x+110 | | 154-7x=29x+18 | | 6-10x=30-31x | | c=1.25(500)+110 | | -(5y+1)-(-4y-5)=3 | | c=1.25x+110 | | (5a)*(7ab)= | | (5a)x(7ab)= | | 2(4-B)=2-B-(B-6) | | 5a^7*ab= | | 2(4-B)=2-B(B-6) | | 15-2m=11 | | 10x-7=8x-1 | | 2x+(3-4)=2x | | x^2-13x-16=0 | | x^2-18x=-7 | | 3(0)-(-5)=5 | | -3-9= | | -3c-9c= | | 0-(-5)= | | 2(x)+0=26 | | 2x+3(0)=26 |

Equations solver categories